CORAK PEMIKIRAN DAN METODE IJTIHAD IBN TAYMIYYAH - Zainal Abidin (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2010)
This article discusses the thought color and methods of ijtihad of Ibn Taymiyyah, one of the most influential figures in the movement of of Islamic thought renewal. He raised a number of criticisms of the logician. The arguments he used indicated that he is a thinker of empiricism. This empiricism complexion coloring intellectual works in various fields. In the field of fiqh, in the beginning he was a follower of the school of Hanbaliyah, however, in further development he performed ijtihad independently without being tied down by other schools. That is why Ibn Taymiyya was known as a mujtahid mutlaq. Although in performing ijtihad he remains grounded in the Qur’an and Sunnah as well as admits the ijmâ’ and qiyâs as a source of Islamic law, his thoughts are often different from other scholars of his time, both on the aspect of methodology and the results of his ijtihad.